2016
DOI: 10.1093/mnras/stw1393
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the [O ii], H β and [O iii] emission line luminosity functions over the last nine billions years

Abstract: Citation for published item:gomp r tD tF nd huD qF nd qonz lezE erezD F nd xor ergD F nd xewm nD tF nd resseD vF nd i h rdD tF nd epesD qF nd unei D tFE F nd i hoorD eF nd r d D pF nd w r stonD gF nd e heD gF nd helu D F nd tulloD iF @PHITA 9 he evolution of the y ss D r nd y sss emission line luminosity fun tions over the l st nine illions ye rsF9D wonthly noti es of the oy l estronomi l o ietyFD RTI @IAF ppF IHUTEIHVUF Further information on publisher's website: Additional information: Use policyThe full-tex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 53 publications
3
55
1
Order By: Relevance
“…4 to the observational compilation done by Comparat et al (2016a) 10 , that includes data from the VVDS-Deep, VVDS-Wide and DEEP2 surveys among others (Ly et al 2007;Gilbank et al 2010;Sobral et al 2012;Drake et al 2013;Ciardullo et al 2013;Khostovan et al 2015). The model LFs are in reasonable agreement with the observations, with differences within a factor of 5 for densities above 10 −5 Mpc −3 h 3 dex −1 .…”
Section: Luminosity Functionssupporting
confidence: 65%
See 4 more Smart Citations
“…4 to the observational compilation done by Comparat et al (2016a) 10 , that includes data from the VVDS-Deep, VVDS-Wide and DEEP2 surveys among others (Ly et al 2007;Gilbank et al 2010;Sobral et al 2012;Drake et al 2013;Ciardullo et al 2013;Khostovan et al 2015). The model LFs are in reasonable agreement with the observations, with differences within a factor of 5 for densities above 10 −5 Mpc −3 h 3 dex −1 .…”
Section: Luminosity Functionssupporting
confidence: 65%
“…The particular filter response used for the different cuts is indicated by a superscript on the magnitude column. Comparat et al (2016a) are shown as filled circles, with colours matching the cuts used to mimic the corresponding survey selection, as indicated in the legend. The observational errors come from jackknife re-sampling (Comparat et al 2016a) and in some cases are smaller than the symbol.…”
Section: Luminosity Functionsmentioning
confidence: 99%
See 3 more Smart Citations